Community Engagement dan Resolusi Konflik Sosial di Era Pandemi: Implementasi dan Kontribusinya terhadap Penguatan Pendidikan Multikultural di Desa Sukorejo - Fikri, Ishom Fuadi; Kusairi, Ahmad (Proceedings of Annual Conference on Community Engagement, 2022)
Sukorejo, one of the villages in Banyuwangi Regency, has experienced social conflicts in 2019 and 2022. This second social conflict coincides with the Level 3 Pandemic situation in Banyuwangi. Through the qualitative method, this research aims to understand; 1) the implementation of the community engagement in social conflict resolutions in Sukorejo Village and 2) its contribution in strengthening the multicultural education in the Pandemic era in Sukorejo Village. The results of this study show that the community engagement in the social conflict resolution is implemented by the Government of Sukorejo Village in collaborating with civil society organizations under the coordination of the Government of Banyuwangi Regency through the mediation approach in 2019, while in 2022 through both mediation and arbitration. The conflict resolution models are peacekeeping, peacemaking, and peacebuilding. The multicultural education plays a role in strengthening the capacity building of human resources in a frame of multiculturalism. Community engagement activities and the multicultural education are mutually corelated, where both of them contribute to each other and meet in the same intersection, i.e. the community empowerment.